2021
DOI: 10.1186/s12879-021-06170-z
|View full text |Cite|
|
Sign up to set email alerts
|

The health-related quality of life in Iranian patients with COVID-19

Abstract: Background COVID-19 is a public health emergency with a high mortality rate and it reduces the patient’s Health-Related Quality of Life (HRQoL) significantly. This effect is measured in the current study. Methods In a cross-sectional study in Iran, 320 randomly selected treated patients from COVID-19 were studied. To collect the required data, we applied a questionnaire that included socio-demographic factors, clinical characteristics, and question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…It was seen that the disease had not only physical signs and symptoms in the short term but also in the long term, and so a condition known as the “long-COVID” syndrome was described ( Cirulli et al, 2020 ; Sudre et al, 2020 ). Since the spread of the disease and it becoming a global crisis, a growing body of evidence has begun to indicate that the clinical picture would not be limited to vital and physical dimensions, and that psychological and social consequences of the disease have also become critical effects across multiple populations ( Ali & Alharbi, 2020 ; Alimoradi et al., 2021 ; Alinia et al., 2021 ; Armbruster & Klotzbücher, 2020 ; X. Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was seen that the disease had not only physical signs and symptoms in the short term but also in the long term, and so a condition known as the “long-COVID” syndrome was described ( Cirulli et al, 2020 ; Sudre et al, 2020 ). Since the spread of the disease and it becoming a global crisis, a growing body of evidence has begun to indicate that the clinical picture would not be limited to vital and physical dimensions, and that psychological and social consequences of the disease have also become critical effects across multiple populations ( Ali & Alharbi, 2020 ; Alimoradi et al., 2021 ; Alinia et al., 2021 ; Armbruster & Klotzbücher, 2020 ; X. Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…While some patients reported being asymptomatic, some non-hospitalized patients reported COVID-19 symptoms that extended well beyond the expected time period for recovery ( Huang et al., 2020 ; Lai et al., 2020 ; Xu et al., 2020 ). Severity of initial symptom presentation, the types of symptoms, as well as functional impairment and physical and psychological health are affected to different degrees ( Alinia et al, 2021 ; Carenzo et al, 2021 ; Temperoni et al, 2021 ). While there is substantial evidence in the literature, especially for hospitalized patients, the functional or daily impacts of non-hospitalized patients are relatively less emphasized.…”
Section: Introductionmentioning
confidence: 99%
“…There was a lack of utility scores for different COVID-19 health statuses in the Chinese population. Thus, we used an Iran study focusing on the health utility value of patients with COVID-19, and the utility scores from the Iran population were more representative of the Asian population and covered all health statuses in our model [ 45 ]. The utility of people of susceptible statuses was referred to in the paper, focusing on the norms for EQ-5D-5L among the Chinese general population, given that the general population does not have full health [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, only few studies have reported HRQoL of patients after discharge. One study has revealed that COVID-19 is associated with a substantial and measurable decrease in HRQoL, and the age and hospitalization status of participants were the key determinants of their COVID-19 health utility value ( 10 ). Further evidence suggests that, even though physical function was recovered, patients might still have mental disorders ( 11 ), which could affect them even after 1 year ( 12 ).…”
Section: Introductionmentioning
confidence: 99%